Promoting healthy eating habits of preschoolers in Malolos through ECLA and FHEM - Saladores, Genevieve T. (2001)
Preschoolers across cultures have been identified to consistently have a high prevalence of nutritional deficiencies and less ideal dietary pattern. The emergence of preschools and day care centers provide the environments that are influencing the eating habits of preschoolers. Thus, it is a challenge for nurses to address these nutritional concerns through nutrition education in the preschool setting.This study determined the effects of a two-pronged intervention, Early Childhood Learning Activities (ECLA) and Family-based Health Education Module (FHEM) to the eating habits of preschoolers. Eating habits was measured by the following dependent variables : (1) recognition of nutritious good; (2) fruit and vegetable intake; (3) preference for natural over processed food; and (4) widening of food preferences. This study also explored the association of selected socio-demographic variables to the preschoolers' eating habits after the two-pronged intervention. Socio-demographic variables are categorized as Child-factors (age, sex, ordinal position) and Family-factors (religion, parents' educational attainment, parents' occupation, monthly family income, family structure, and FHEM recipient).The study has utilized two pre-experimental research designs: post test - only for the single variable, recognition of nutritious food; and one-group pre-test-posttest design for the rest of the variables. The sample consisted of 21 preschoolers enrolled in Daily Vacation Bible Study of Emmaus Kindergarten in Malolos, Bulacan; and their parents / caregivers.Instruments used are two-pronged intervention: ECLA and FHEM and pretest/posttest Food Diary Forms. the ECLA are five nutrition learning activities implementing to the preschoolers and FHEM is a nutrition module for their parents/caregivers. Food Diary Forms recorded the three-day food intake of the preschoolers, pre- and post-intervention. It also contained their socio-demographic profile. Qualitative data were also gathered utilizing in-depth interviews.Significant findings showed: (1) a positive effect of ECLA on preschoolers' recognition of nutritious food; (2) positive difference between pre-test and post-test eating habits, specifically on: presence of vegetable intake, preference for natural over processed good, and widening of good preferences. Inferential statistics used were Wilcoxon Signed Ranks Test, McNemar Test and Paired T-test. Among the socio-demographic variables (Child and Family factors), the following were found to be associated with the outcomes of intervention, based on qualitative analysis: parents' education level, father's occupation, FHEM recipient are positively associated; mother's occupation and family size are negatively associated. However, when subjected to statistical analysis, all socio-demographic variables are not significantly associated with eating habits of preschoolers post-intervention.Based on the findings of this study the following recommendations were made: reinforced the health educator role of the nurse, involving the preschoolers as recipients; design and implement early childhood health education, especially on nutrition; advocate the integration of health promotion activities to school curricula through the Child and Youth Welfare Act; include the preschools as clinical area for student nurses. It is likewise recommended that similar studies be conducted to enhance the instruments used and to identify other variables correlating with eating habits of preschoolers.
Thesis (Master of Arts in Nursing)--University of the Philippines Manila.
Keywords: Children -- Nutrition; Food habits